Suppression of Δlon phenotypes in Escherichia coli by N‐terminal DnaK peptides. (7th January 2019) - Kumaran, Nagarajan; Munavar, M. Hussain
Abstract : Δ lon mutant of Escherichia coli becomes hypersensitive to DNA damaging agents and over‐produce capsule due to stabilization of the Lon substrates, namely, SulA and RcsA, respectively. These phenotypes were earlier found to be suppressed in Δlon ssrA::cat /pUC4 K and Δlon faa (DnaJ, G232D) strains, called as "Alp" strains. We observed that a plasmid carrying an E. coli chromosomal fragment harboring few genes, a heat shock gene htpY and a portion of dnaK capable of encoding truncated N‐terminal ATPase domain (244 aa) could suppress lon mutant phenotypes. Deletion of htpY did not affect the efficiency of suppression. Clones expressing DnaK′ (244 aa) peptide alone could suppress both Δlon phenotypes in copy number dependent manner. Inactivation of clpQ did not affect the MMS R phenotype of Δlon strain carrying dnaK ′ clones indicating that ClpYQ protease does not degrade SulA. We hypothesize that the high levels of defective DnaK′‐DnaJ chaperone complex formed in these strains might lead to aggregation of SulA and RcsA and, thereby the suppression of Δlon phenotypes. Systematic deletion analysis of dnaK ′ revealed that, ∼220 aa N‐terminal DnaK peptide is required for suppression of cps‐lac over‐expression and ∼169 aa peptide is enough for the suppression of MMS S phenotype of Δ lon mutant.